Urgensi pendidikan adab dan akhlak di sekolah dasar menuju generasi emas 2045 - Frandani, Muhammad; Yuhdi, Yuhdi; Abdul Aziz, Hamdan; Riska, Riska; Irmayanti, Mutia (Program Studi Magister Pendidikan Agama Islam, 2024)
Moral degradation and moral crisis in children seem to be an endless problem. It has been more than 10 years since the establishment of character education as a National Movement to overcome the moral crisis in society. Until now, the practice of intolerance, sexual violence and bullying is still entrenched in children. This even happened in the elementary school environment. The golden generation of 2045, which is projected as a gift for 100 years of Indonesian independence, seems to be still far from expectations. Moreover, the COVID-19 pandemic which for the past two years has hindered the process of strengthening character education for children. The purpose of this study is to analyze the urgency of etiquette and moral education for elementary school age children towards the golden generation of 2045. The method used is a qualitative method with a library research approach. The results of this study indicate that it is very urgent for adab and moral education to be applied to elementary school age children. Where this phase is a golden phase in the formation of human character and character which is expected to later become an important foundation for realizing the 2045 Golden Generation. Abstrak Degradasi moral dan krisis akhlak pada anak seolah menjadi permasalahan yang tidak berujung. Sudah lebih 10 tahun sejak ditetapkannya pendidikan karakter sebagai Gerakan Nasional untuk mengatasi krisis moral di masyarakat. Sampai saat ini, praktik intoleransi, kekerasan seksual dan perundungan masih membudaya pada anak-anak. Bahkan hal tersebut terjadi di lingkungan Sekolah Dasar. Generasi emas 2045 yang diproyeksikan sebagai hadiah 100 tahun kemerdekaan Indonesia agaknya masih jauh dari harapan. Terlebih lagi pandemi COVID-19 yang selama dua tahun belakang menghalangi proses penguatan pendidikan karakter pada anak. Tujuan dari penelitian ini adalah untuk menganalisis urgensi pendidikan adab dan akhlak untuk anak usia SD menuju generasi emas 2045. Adapun metode yang digunakan adalah metode kualitatif dengan pendekatan studi kepustakaan (library research). Hasil penelitian ini menunjukkan bahwa pendidikan adab dan akhlak sangat urgen diterapkan untuk anak usia sekolah dasar. Di mana fase ini adalah fase emas dalam pembentukan karakter dan watak manusia yang diharapkan nantinya menjadi pondasi penting untuk mewujudkan Generasi Emas 2045.